Discourse Patterns and Interaction in English Learning Discussions on Social Media - Sofia Nazarani; Dinar Amelia Godina; Diva Aprilia; Khabibatun Najmi Ramadhani; Sofie Amalia Hapsari; Cempaka Amalia Putri; Dewi Puspitasari (Universitas Stikubank (UNISBANK) Semarang, 2026)
This study discusses communication patterns that appear in discussions about learning English on social media, especially on Twitter. Nowadays, social media is often used to share experiences, opinions, and find information, including topics related to learning English. In online discussions, users not only express their ideas but also interact with each other through comments and replies, creating communication patterns that are interesting to study. This research uses a qualitative approach with discourse analysis. The data were taken from three discussion threads focusing on learning English, such as difficulties in speaking, learning methods, and learning experiences from various media. The data were then analyzed to identify the communication patterns, how users start and respond to discussions, and how interactions develop in online conversations. The results show several common patterns, such as problem–solution, sharing experiences, and giving direct advice. Users usually start discussions by asking questions, sharing experiences, or expressing opinions, while the responses vary from suggestions and short opinions to personal experiences. Interactions develop through comment replies and the exchange of ideas, although they are usually brief and casual. This shows that social media can be a supportive space for learning English informally through everyday interactions.